The Pattern of Stability and Change in Parental Locus of Control Over 6 Years and Teacher Ratings of Child Behavior - Nowicki, Stephen; Gregory, Steven; Ellis, Genette L.; Iles-Caven, Yasmin; Golding, Jean (Frontiers in Psychology, 2018)
A previous study from our group showed that parents’ locus of control (LOC) obtained prior tobefore their child’s birth of their child was associated with the child’s behavior at school in School Years 3 (ages 7–8) and School Year 6 (ages 10–11). Here we examine whether a change in parental LOC over the first six years of the child’s life was associated with differences in his or her behavior as rated by their teachers. As before we We used data from the Avon Longitudinal Study of Parents and Children (ALSPAC). Both parents completed Aa modified version of the adult Nowicki–Strickland internal–external locus of control scale was completed by mothers and fathers in their own home during pregnancy and six years later. Internality was defined as a score equal to, or less than, the median and externality was defined as a score greater than the median. and internality as equal to, or less than, the median. The outcomes considered were the five individual subscales and the total difficulties of Goodman’s Strengths and Difficulties Questionnaire (SDQ) completed at the end of School Years 3 and 6 by the children’s class teachers. at the end of School Years 3 and 6. As predicted, we found that parents who remained externally oriented, or became external, had children with more behavioral difficulties in primary school compared with parents who remained or became internal. Type of behavior difficulties varied somewhat with whether mothers or fathers remained or changed toward externality. These results support the possibility that changes in parental LOC are associated with children’s personal and social adjustment. Consequently, programs to change parental LOC are worth evaluating.